EFEK PAJAK HOTEL DAN PAJAK RESTORAN SEBAGAI SUMBER PENDAPATAN PAJAK DAERAH KOTA BATU (Studi Pada Dinas Pendapatan Daerah Kota Batu) - Lalityasari, Ayu Rahajeng (Jurnal Mahasiswa Perpajakan, 2014)
This study uses explanatory research with quantitative approach. The population in this research is all data of monthly time series revenue of hotel tax and restaurant tax. The selection of the samples is based on the monthly time series data in the period of January 2010 – December 2012, which are 36 samples. The data was obtained from Local Revenue Office of Batu City. The analysis of the data employs double linear statistic regression by using SPSS 19.0 program. The determination coefficient value (R2) of 0.018 means that free variables of hotel tax and restaurant tax explains bound variables of local tax revenue of 81.8% while the rest (18.2%) is explained by other unstudied variables. The result of simultaneous test (F Test) shows that hotel tax and restaurant tax have simultaneously significant effects on local tax revenue. Meanwhile, the result of partial test (t Test) shows that hotel tax and restaurant tax variables have significant effects on local tax revenue. It is also evidence that restaurant tax has the most dominant effect because it has the biggest beta coefficient value and t count. Based on these results, it is suggested that Local Revenue Office of Batu City pay more attention to hotel tax and restaurant tax revenue so that it can increase the revenue and the office should also tighten the administration sanctions for the taxpayers performing tax violation because these sanctions are more effective in decreasing hotel tax and restaurant tax arrears Keyword: Hotel and Restaurant Tax Batu City, Local Tax Revenue, Hotel Tax Revenue, Restoran Tax Revenue